Causal links in QOL sub-domains accentuate greater support for physical and emotional well-being of breast cancer survivors - Abu Kassim , Noor Lide; Mohd Hanafiah, Khayriyyah; Samad Cheung, Humairah; Rahman, Mohammad Tariqur (2010)
Group psychotherapy or support group (SG) interventions have been reported to improve the quality of life (QOL) of cancer patients. For an improved life of Malaysian breast cancer survivors, facilities for SG interventions have been set up both in the urban and rural areas of the country. However, the impact of support group participation on QOL of these patients, and factors that may influence it have remained elusive. This study, examines the impact of SG participation on the QOL of Malaysian breast cancer survivors using the Functional Assessment of Chronic Illness Therapy (FACIT) questionnaire. Multiple comparisons using the Tukey HSD show that the QOL measure for rural SG participants are significantly lower (F(2,55) = 14.570; p < 0.01) than for urban SG participants. Analysis of the interrelationships between the QOL sub-domains indicated that functional wellbeing (FWB) fully mediates the effects of physical wellbeing (PWB) and emotional wellbeing (EWB) on social wellbeing (SWB). In addition, PWB was relatively more influential than EWB in determining patients’ FWB and SWB while PWB, EWB and FWB collectively explained about 25% of the variability in SWB. Findings of this study thus indicate that measurement of QOL is relative to patients’ location i.e., urban or rural, which in turn reflects the patients’ education and financial background.